Aerosol optical thickness (AOT) retrieval over land using satellite image-based algorithm - Hadjimitsis, Diofantos G. (Air quality, atmosphere and health, 2009)
The aim of this study is to present and apply the proposed algorithm on archived time series Landsat TM over an urban area in the vicinity of Heathrow Airport (UK) acquired in 1984–1986 and to two up-to-dated Landsat TM images in the vicinity of Paphos Airport in Cyprus acquired in July–August 2008. The monitoring of aerosol concentrations becomes a high environmental priority particularly in urban areas. The proposed algorithm has been developed to allow the quantification of the aerosol optical thickness (AOT) over land. The algorithm compares multitemporal satellite data sets and evaluates radiometric alterations due to the optical atmospheric effects of aerosols. Novel features of this algorithm which is based on the application of radiative transfer calculations are the inclusion of applying iteration procedures for selecting the suitable object for determining the aerosol optical thickness and the automatic division into working grid cells. AOT retrieval from Landsat TM band 1 images of Cyprus has been cross-validated satisfactorily by comparing AOT values found from handheld MICROTOPS II sun photometer.